How the Buddhist concept of Right Speech would be applied towards diplomatic actions using the media: a case study from the 2002 State of the Union - Stout, Daniel R. (Kansas State University, 2009)
Communication between countries is an essential part of international relations. Leaders use the media to build confidence, advance negotiations or garner political support. This process is identified as media diplomacy. Television is an important part of international relations, and some have even gone so far to say that ambassadors between countries serve nothing more than a social function. In this analysis it is argued that current strategies of media diplomacy do lead to violence because they encourage power plays, violence, and overemphasis on national ego. The proposed alternative is to embrace a Buddhist alternative identified as Right Speech to overcome current deficiencies. The study found that President Bush’s 2002 State of the Union violated the tenets of Right Speech. The implications of violations including the increased likelihood of violence between nation states will be discussed.
Keywords: Buddhism; Right speech; Skillful speech; State of the union; Religion, Philosophy of (0322); Speech Communication (0459)